2019
DOI: 10.3390/min9010066
|View full text |Cite
|
Sign up to set email alerts
|

Unique PGE–Cu–Ni Noril’sk Deposits, Siberian Trap Province: Magmatic and Tectonic Factors in Their Origin

Abstract: The unique and very large PGE–Cu–Ni Noril’sk deposits are located within the Siberian trap province, posing a number of questions about the relationship between the ore-forming process and the magmatism that produced the traps. A successful answer to these questions could greatly increase the possibility of discovering new deposits in flood basalt provinces elsewhere. In this contribution, we present new data on volcanic stratigraphy and geochemistry of the magmatic rocks in the key regions of the Siberian tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 61 publications
0
12
1
Order By: Relevance
“…Compressional forces and tectonic activity ceased within the Taimyr-Severnaya Zemlya fold-and-thrust belt during the Early Permian, and it has subsequently formed the northern margin of the Siberian Craton (Kurapov et al, 2020;Vernikovsky, 1996). Various researchers (Khain et al, 1991;Saunders et al, 2005;Dobretsov et al, 2013a;Afanasenkov et al, 2016;Krivolutskaya et al, 2019) propose an extensional environment close to Siberian margins and within the West Siberian basin in the Late Permian-Early Triassic. Particularly, the development of the Yenisei-Khatanga paleo-rift (Krivolutskaya et al, 2019) suggests that synchronous extension could appear within the Taimyr-Severnaya Zemlya foldand-thrust belt.…”
Section: ■ Geological Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…Compressional forces and tectonic activity ceased within the Taimyr-Severnaya Zemlya fold-and-thrust belt during the Early Permian, and it has subsequently formed the northern margin of the Siberian Craton (Kurapov et al, 2020;Vernikovsky, 1996). Various researchers (Khain et al, 1991;Saunders et al, 2005;Dobretsov et al, 2013a;Afanasenkov et al, 2016;Krivolutskaya et al, 2019) propose an extensional environment close to Siberian margins and within the West Siberian basin in the Late Permian-Early Triassic. Particularly, the development of the Yenisei-Khatanga paleo-rift (Krivolutskaya et al, 2019) suggests that synchronous extension could appear within the Taimyr-Severnaya Zemlya foldand-thrust belt.…”
Section: ■ Geological Settingmentioning
confidence: 99%
“…Various researchers (Khain et al, 1991;Saunders et al, 2005;Dobretsov et al, 2013a;Afanasenkov et al, 2016;Krivolutskaya et al, 2019) propose an extensional environment close to Siberian margins and within the West Siberian basin in the Late Permian-Early Triassic. Particularly, the development of the Yenisei-Khatanga paleo-rift (Krivolutskaya et al, 2019) suggests that synchronous extension could appear within the Taimyr-Severnaya Zemlya foldand-thrust belt. Vernikovsky et al (2003) reported U-Pb zircon ages of several syenite-granite intrusions from northwestern Taimyr (Fig.…”
Section: ■ Geological Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…The Ni/Pd versus Cu/Ir diagram shows most samples are in the range of high Mg basalt (Figure 10b). The genetic relationships are also suggested by the Ni/Cu ratios, which are lower than that segregated from komatiitic magmas (>7, [2]), but comparable with basalt magmas such as those from the Nadezhdinsky Formation at the Noril'sk region (~1, [61][62][63]) and Sudbury in Canada (1.2, [12]). The MgO content of parental magma of the Jinchuan intrusion was estimated to be 11.5-12.6 wt.% [17,30,64].…”
Section: Prior Sulfide Segregationmentioning
confidence: 99%
“…This study is focused on the Kulyumber area located in the middle part of the Kulyumber river valley which represents one of the least studied areas of the province (Figure 1). It is located between the Tunguska syncline and Norilsk-Igarka zone [48][49][50] and thus it provides information on the magmatic events within both structures at the Permian-Triassic boundary (250 ± 0.3 Ma; [51]). Within this territory effusive rocks and numerous intrusive bodies were found during the geological mapping.…”
Section: Introductionmentioning
confidence: 99%